Serum Copper, Zinc, Calcium And Magnesium Levels In Mothers With Offspring Affected By Neural Tube Defects: A Case-Control Study - Taboada Lugo, Noel; Mollineda Trujillo, Ángel; Herrera Martínez, Manuela (Revista Cubana de Investigaciones Biomédicas, 2019)
Background: Neural tube defects (NTDs) are important causes of infant mortality, which result from a complex interaction between genetics and environmental factors such as trace elements, which play and crucial role in the epigenetic regulation in the embryo fetal developmental program. Objectives: To measure the maternal serum levels of copper, zinc, calcium and magnesium in mothers with offspring affected by NTDs, and to examine a possible relationship between the serum concentrations of these micronutrients and occurrence of NTDs. Design: Case-controls study. Subjects and Methods: Maternal serum blood samples were obtained from 72 healthy pregnant women and 36 mothers who had NTDs affected offspring, including those alive, stillbirths and elective pregnancy’ termination at Centro Provincial de Genetica in Villa Clara. Copper, zinc, calcium and magnesium levels in serum were measured by flame atomic absorption spectrometry and were compared between the two groups of mothers. Results: Serum zinc levels were determined to be significantly lower in the study group compared with the control group, while copper levels were significant elevated in the study group (all p values < .05). There was a negative correlation between serum zinc levels and serum copper levels. However, no association between calcium and magnesium serum levels and increased risk for the development of NTDs was observed. Conclusions: High maternal serum levels of copper and lower level of zinc during pregnancy were associated with NTDs in offspring. If folic acid supplementation is given, additional zinc supplementation should be considered for the further decrease in the recurrence risk of NTDs.